Creating Sustainable Content by Integrating Cultural Heritage on Instagram - Tedjakumala, Ingrid; Damayanti, Ninis Agustini; Mulyana, Deddy; Perbawasari, Susie (Interdisciplinary Social Studies, 2023)
Background: With the extensive research conducted on millennials and their behaviors, most resulting in understanding the generations as the digital generations who are always been stereotype and linked to negative adjectives. Aim: This research explores the various cultural heritage information use as Instagram content on a single origin coffee brand from Flores, Indonesia and gain a better understanding on how cultural heritage can become a sustainable content as an approach to digital marketing strategy. Method: The research was conducted on thirty Instagram followers of a single-origin coffee brand based in Jakarta, that uses coffee originating from Sikka, Flores. Findings: The descriptive analysis result from surveys and follow-up interviews resulting in three main archetypal characteristic of Indonesian Millennials in Jakarta who are more appreciative towards unorthodox content post on the brand’s Instagram account.